2021
DOI: 10.1002/jclp.23251
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing the couple relationship to prevent suicide: A preliminary examination of Treatment for Relationships and Safety Together

Abstract: Objective: To evaluate the feasibility, preliminary effects, and acceptability of the first comprehensive couple-based treatment for suicide, called Treatment for Relationships and Safety Together (TR&ST). Method: In a preliminary examination, five couples (N = 10) participated in 10 weekly sessions of TR&ST. All couples included a veteran who reported active suicidal ideation at baseline and their partner. Couples completed measures of relationship functioning, perceived burdensomeness, thwarted belonging, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The factors of thwarted belongingness and perceived burdensomeness have been posited to be causes of suicidality, 43 hence couple therapy to rebuild connection and mutual understanding in couples should be researched as a viable intervention to prevent and reduce suicidality. In a recent purportedly first comprehensive couple‐based suicide‐specific intervention study with 5 veterans and their partners, results showed improved couple relationship and decreased perceived burdensomeness, thwarted belonging, and suicidal ideation, suggesting the feasibility and acceptability of a couple-based suicide prevention as an additional avenue for suicide prevention in veterans 46 . The potential of using couple-based interventions in suicide prevention warrants further examination and research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The factors of thwarted belongingness and perceived burdensomeness have been posited to be causes of suicidality, 43 hence couple therapy to rebuild connection and mutual understanding in couples should be researched as a viable intervention to prevent and reduce suicidality. In a recent purportedly first comprehensive couple‐based suicide‐specific intervention study with 5 veterans and their partners, results showed improved couple relationship and decreased perceived burdensomeness, thwarted belonging, and suicidal ideation, suggesting the feasibility and acceptability of a couple-based suicide prevention as an additional avenue for suicide prevention in veterans 46 . The potential of using couple-based interventions in suicide prevention warrants further examination and research.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent purportedly first comprehensive couple-based suicide-specific intervention study with 5 veterans and their partners, results showed improved couple relationship and decreased perceived burdensomeness, thwarted belonging, and suicidal ideation, suggesting the feasibility and acceptability of a couple-based suicide prevention as an additional avenue for suicide prevention in veterans. 46 The potential of using couple-based interventions in suicide prevention warrants further examination and research.…”
Section: Suicidality and Couple Therapymentioning
confidence: 99%
“…These interventions should be tailored to context and needs, with family interventions being flexible enough to attend to the various roles within the family, the adult–adult dynamic, and differing experiences and perspectives. Research aiming to develop effective couple interventions which incorporate these elements is beginning to emerge (Khalifian et al., 2022), however current family‐based interventions are predominantly tailored to families where the suicidal individual is an adolescent (Ougrin et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, recent years have seen growing attention to adult relationships through “indicated prevention”—treatments designed for families of individuals with recent ideation or attempts. Studies include a 6‐session conjoint safety planning protocol (Goodman et al, 2022), a 10‐session behavioral couple therapy program (Khalifian et al, 2022), a 15‐week intensive outpatient program (Anastasia et al, 2015), and a 6‐month post‐discharge telephone protocol (Miller et al, 2016). However, it can be difficult to engage supportive family members in times of crisis, with the largest study of a family approach after suicide‐related emergency department visits finding only 20% of patients had a family member engage in the treatment (Miller et al, 2017).…”
Section: Introductionmentioning
confidence: 99%